Chapter Lavoro, tecnica e società in Platone: uno sguardo d’insieme - FERRARI, Franco (Firenze University Press, 2025)
During the 5th century B.C., skills (technai), including manual ones, assume an exceptional role in Greek society and culture. Plato's attitude appears to be twofold: on the one hand he credits the possessors of these skills as having objective and efficacious knowledge, on the other hand he devalues, probably for ideological and social reasons, manual techniques. On the economic and social level, techniques play a fundamental role in the existence of humans, who, due to their lack of self-sufficiency, are inclined to cooperate by sharing their technical and professional skills. Each individual is part of the city to the extent that he possesses and exercises a technique. Plato also attaches great importance to commercial activity and the use of money. In his last work, the Laws, he seems to devalue the role of techniques within the city: membership of the polis is no longer given by the possession of a technique, but by land property.